Math with capital letters. Reknowing it and reknowing ourselves: An urgent relinking mathematics - Rodríguez, Milagros Elena (Revista Hipótese, 2022)
was analyzed with a capital letter, as reknowing it and re-knowing ourselves in it from the interiority of being is urgent. It is a socialcultural spiritual construct defined in wishes and acknowledgments to shape generations in the awareness of the contributions of science legacy of humanity, as essential in citizenship. The rhizomatic deconstruction was carried out with the transmethod; where the possibility of recognizing ourselves is combined in the complex and transdisciplinary. In conclusion, as a symbolic scenario, mathematics is configured by society according to its convictions and beliefs about what the human being and the world should be.